Association between OX40L polymorphism and type 2 diabetes mellitus in Iranians - Jahromi, Abdolreza Sotoodeh; Erfanian, Saiedeh; Roustazadeh, Abazar (BMC medical genomics, 2024)
Diabetes mellitus (DM) is one of the leading causes of morbidity and mortality worldwide. It is a multifactorial disease that genetic and environmental factors contribute to its development. The aim of the study was to investigate the association of OX40L promoter gene polymorphisms with type 2 diabetes mellitus (T2DM) in Iranians. Three hundred and sixty-eight subjects including 184 healthy subjects and 184 T2DM patients were enrolled in our study. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was applied to detect genotype and allele frequencies of rs3850641, rs1234313 and rs10912580. In addition, SNPStats web tool was applied to estimate haplotype frequency and linkage disequilibrium (LD). The distribution of tested polymorphisms was statistically different between the T2DM patients and healthy subjects (P < 0.01). rs1234313 AG (OR = 0.375, 95% CI = 0.193-0.727, P = 0.004) and rs10912580 AG (OR = 0.351, 95% CI = 0.162-0.758, P = 0.008) genotypes were associated with the decreased risk of T2DM in Iranians. Moreover, our prediction revealed that AAG (OR = 0.46, 95% CI= (0.28-0.76), P = 0.0028) and GAG (OR = 0.24, 95% CI= (0.13-0.45), P < 0.0001) haplotypes were related to the reduced risk of the disease. However, the tested polymorphisms had no effect on biochemical parameters and body mass index (BMI) in the patient group (P > 0.05). Our findings revealed that OX40L promoter gene polymorphisms are associated with T2DM. Moreover, genotype and allelic variations were related to the decreased risk of T2DM in Iranians. Further studies are recommended to show whether these polymorphic variations could affect OX40/OX40L interaction or OX40L phenotype.